A study of sample entropy towards process capability - Zhang, Zheng (Kansas State University, 2015)
The process capability is a measurable property of a process related to the specification of a product. Traditionally, process capability analysis (PCA) measurements are expressed by a process capability ratio (PCR). When using a typical PCR to measure process capability, there are certain assumptions, and critics have been made towards PCR, that some the assumptions are violated. Much research has been conducted to ratify the situations when some of the assumptions are violated. This thesis, is going to demonstrate a research towards process capability using Sample Entropy method. The desirable outcome would be that this method can avoid violating the assumptions.
Keywords: Quality control; Process capability analysis; Process capability ratio; Sample entropy; Engineering (0537)